Strategizing across organizations capitalizing on big opportunities and solving systemic problems will require organizations to come together to develop strategies as a group - Ramírez, Rafael; Lang, Trudi; Finch, Matthew; Carson, Gail; Fisher, Dale (MIT Sloan Management Review, 2023)
Tackling the big, systemic challenges confronting many organizational business leaders will increasingly require strategizing across organizational boundaries, but doing so is more complex than making strategy within a single organization. The authors developed a new approach to collaborative strategy in working with a global public health organization. Lessons learned can help leaders in individual organizations work with others to achieve both shared and individual strategic priorities.
"Reprint 64327.". - Includes bibliographical references
Keywords: Organizational effectiveness; Organizational change; Efficacité organisationnelle; Changement organisationnel